Study of Awareness, Enrollment, and Utilization of Rashtriya Swasthya Bima Yojana (National Health Insurance Scheme) in Maharashtra, India - Thakur, Harshad (Front Public Health, 2016)
INTRODUCTION: Government of India launched a social health protection program called Rashtriya Swasthya Bima Yojana (RSBY) in the year 2008 to provide financial protection from catastrophic health expenses to below poverty line households (HHs). The objectives of the current paper are to assess the current status of RSBY in Maharashtra at each step of awareness, enrollment, and utilization. In addition, urban and rural areas were compared, and social, political, economic, and cultural (SPEC) factors responsible for the better or poor proportions, especially for the awareness of the scheme, were identified. METHODS: The study followed mixed methods approach. For quantitative data, a systematic multistage sampling design was adopted in both rural and urban areas covering 6000 HHs across 22 districts. For qualitative data, five districts were selected to conduct Stakeholder Analysis, Focused Group Discussions, and In-Depth Interviews with key informants to supplement the findings. The data were analyzed using innovative SPEC-by-steps tool developed by Health Inc. RESULTS: It is seen that that the RSBY had a very limited success in Maharashtra. Out of 6000 HHs, only 29.7% were aware about the scheme and 21.6% were enrolled during the period of 2010–2012. Only 11.3% HHs reported that they were currently enrolled for RSBY. Although 1886 (33.1%) HHs reported at least one case of hospitalization in the last 1 year, only 16 (0.3%) HHs could actually utilize the benefits during hospitalization. It is seen that at each step, there is an increase in the exclusion of eligible HHs from the scheme. The participants felt that such schemes did not reach their intended beneficiaries due to various SPEC factors. DISCUSSION AND CONCLUSION: The results of this study were quite similar to other studies done in the recent past. RSBY might still be continued in Maharashtra with modified focus along with good and improved strategy. Various other similar schemes in India can definitely learn few important lessons such as the need to improve awareness, issuing prompt enrollment cards with proper details, achieving universal enrollment, ongoing and prompt renewal, and ensuring proper utilization by proactively educating the vulnerable sections.